Evidence shortfalls in the recommendations and guidance underpinning ecological mitigation for infrastructure developments. Issue 3 (30th July 2021) - Hunter, Sara B.; zu Ermgassen, Sophus O. S. E; Downey, Harriet; Griffiths, Richard A.; Howe, Caroline
Abstract: In the United Kingdom and European Union, legal protection of species from the impacts of infrastructure development depends upon a number of ecological mitigation and compensation (EMC) measures to moderate the conflict between development and conservation. However, the scientific evidence supporting their effectiveness has not yet been comprehensively assessed. This study compiled the measures used in practice, identified and explored the guidance that informed them and, using the Conservation Evidence database, evaluated the empirical evidence for their effectiveness. In a sample of 50 U.K. housing applications, we identified the recommendation of 446 measures in total, comprising 65 different mitigation measures relating to eight taxa. Although most (56%) measures were justified by citing published guidance, exploration of the literature underpinning this guidance revealed that empirical evaluations of EMC measure effectiveness accounted for less than 10% of referenced texts. Citation network analysis also identified circular referencing across bat, amphibian and reptile EMC guidance. Comparison with Conservation Evidence synopses showed that over half of measures recommended in ecological reports had not been empirically evaluated, with only 13 measures assessed as beneficial. As such, most EMC measures recommended in practice are not evidence based. The limited reference to empirical evidence in published guidance, as well as the circular referencing, suggests potential 'evidence complacency', in which evidence is not sought to inform recommendations. In addition, limited evidence availability indicates a thematic gap between conservation research and mitigation practice. More broadly, absence of evidence on the effectiveness of EMC measures calls into question the ability of current practice to compensate for the impact of development on protected species, thus highlighting the need to strengthen requirements for impact avoidance. Given the recent political drive to invest in infrastructure expansion, high‐quality, context‐specific evidence is urgently needed to inform decision‐making in infrastructure development. Abstract : This study evaluates the evidence to support the effectiveness of protected species mitigation measures applied to infrastructure developments. We find that both the recommendations in ecological reports and the guidance informing them are unsupported by scientific evidence, highlighting the need for improved documentation and evaluation of development outcomes.